Dimethyl ether conversion to hydrocarbons on the closely interconnected FER@ZSM-5 nanostructures - Kim, Jong Jin; Jeong, Dong Jae; Jung, Hyun Seung; Hur, Young Gul; Choung, Jin Woo; Baik, Joon Hyun; Park, Myung June; Chung, Chan Hwa; Bae, Jong Wook (Microporous and Mesoporous Materials, 2022)
A superior catalyst activity and stability for dimethyl ether (DME) conversion to gasoline-range hydrocarbons (DTG) on a novel hierarchically-structured hybridized FER@ZSM-5 were verified in terms of the strong interactions of ZSM-5 on the plate-like FER nanostructures, which were prepared by alcohol additive with two organic structure-directing agent (OSDA). The highly active nanostructured FER@ZSM-5 with a propanol additive showed the closely interconnected and highly dispersed ZSM-5 aggregates on the larger plate-like FER surfaces, which were mainly responsible for the suppressed heavy coke depositions with the help of the closely interconnected ZSM-5 and FER interfaces with abundant acidic sites on 8-membered ring (8-MR) channels. The well-dispersed ZSM-5 nanoparticles on Brønsted acid sites of FER surfaces showed coke-resistant natures for DTG reaction due to the synergy effects of the strong acidic sites of the smaller ZSM-5 particles and larger Brønsted acid sites on the plate-like FER structures.
Keywords: Acid site; Acidic sites; Alcohol additives; Catalytic stability; Composited; Dimethyl ether to gasoline; FER/ZMS-5 nanostructure; Gasoline-range hydrocarbons; Nano-composited zeolite; Superior catalysts; Alcohol additives; Catalytic stability; Dimethyl ether (DME) to gasoline (DTG); FER/ZMS-5 nanostructures; Nano-composited zeolite